PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN GURU TENTANG KELAINAN REFRAKSI DI SD NEGRI NGRUKEMAN KASIHAN BANTUL YOGYAKARTA - Januar Rizqi (PSIK 11 UMY, 2011)
The number of refractive disorder in Indonesia increased with a prevalence of 1.5% compared with Southeast Asian countries such as Bangladesh, India and Thailand. Uncorrected refractive disorder in children causes low vision problems and even blindness. Teacher is a person who is considered as a person closest to the children after the parents. Teachers are expected to have the capability in prevention, early detection, and find for appropriate assistance. The objective of this study was to ex